Are Ankylosing Spondylitis Patients at Risk for Poor Total Hip Replacement Outcomes - Costa, C (2017)
Hip involvement in Ankylosing Spondylitis is common and leads to physical and function restriction. Hip replacement surgery is a successful and effective treatment for end-stage hip involvement; however in Ankylosing Spondylitis patient’s prosthesis long-term survival is lesser than other causes of hip osteoarthritis. We report a case of 61-year old Ankylosing Spondylitis male patient with bilateral cementless hip replacement with 26-year and 25-year follow-up.